Efficient scheduling and routing for heterogeneous instant delivery orders: A multi-objective optimization approach with real-time adaptability - Rana Kocsi Vabalas; Miloslavskaya Snyder Grillo; Wang Sheu Nguyen; Skobelev Bock (International Journal of Enterprise Modelling, 2022)
Efficient scheduling and routing of heterogeneous instant delivery orders pose significant challenges in achieving timely and cost-effective delivery operations. In this research, we propose a multi-objective optimization approach with real-time adaptability to address these challenges. We formulate a mathematical model that considers factors such as distance, importance of orders, capacity constraints, time windows, and cost per unit distance or time. The model aims to minimize the overall cost while optimizing the assignment of delivery orders to delivery agents and determining the corresponding routes. We present a numerical example to illustrate the application of the model and discuss the results obtained. The findings highlight the effectiveness of the proposed approach in achieving efficient scheduling and routing, leading to improved resource utilization, cost reduction, and enhanced customer satisfaction. This research contributes to the field of instant delivery services by providing a systematic framework that can be employed to optimize operations in real-world delivery scenarios